Plant-Mediated Effects of Water Deficit on the Performance of Tetranychus evansi on Tomato Drought-Adapted Accessions - Ximénez-Embún, Miguel G.; González-Guzmán, Miguel; Arbona, Vicent; Gómez-Cadenas, Aurelio; Ortego, Félix; Castañera, Pedro (Frontiers in Plant Science, 2018)
Climate change is expected to increase drought periods and the performance and dispersal of some invasive species like Tetranychus evansi, which has been reported to take advantage of the nutritional changes induced by water-shortage on the tomato cultivar Moneymaker (MM). We have examined the implications for mite´s biology of four accessions of the drought-adapted tomatoes, ‘Tomàtiga de Ramellet’ (TR), under moderate drought stress. Mite performance was enhanced by drought in two accessions (TR61 and TR154), but not in the other two accessions (TR58 and TR126). We selected one accession of each outcome (i.e. TR154 and TR126) to further analyse plant nutritional parameters. We found that free sugars and most essential amino acids for mites were induced by drought and/or mite infestation on MM and TR154 plants, whereas sugars were not altered and a reduced number of essential amino acids were induced by drought in TR126. Remarkably, mite performance was enhanced by leaf infiltration of free sugars, essential amino acids mixture and L-proline on well-watered MM and by free sugars on drought stressed TR126 plants. These results indicate a positive link between the induction of soluble carbohydrates and amino acids used by the plant for osmotic adjustment and mite performance. The effects of drought and/or mite infestation on the defense response of plants was analyzed at three levels: phytohormone accumulation, the transcript levels of marker genes linked to jasmonates (JAs), salicylic acid (SA) and abscisic acid (ABA) pathways and the activity of defense proteins. The ability of T. evansi to down-regulate the accumulation of defense-related phytohormones was noted on MM and the two TR accessions analyzed (TR126 and TR154), though differences in the induction of protein defense genes and activities by drought and/or mite infestation were observed among them. These results emphasize the importance of studying plant biotic and abiotic stress factors in combination and provides an experimental framework for screening drought-tolerant tomato accessions that will be also resistant to herbivore mites.